(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
The present report aims to present the actions developed in an extension project of the Universidade Católica Dom Bosco (UCDB) in Campo Grande/MS, which is called “Citizenship without borders”. Therefore, for better organization, we have divided the text into three sections. Being that in the first section, we weave some discussions about the concept and the importance of the university extension. Subsequently, in the second section, we present characteristics of the “Citizenship without borders” project and in the third section, we present some of the results obtained with the project throughout the year 2021. We know that the theme of migration and refuge is on the agenda in several researches , media and governmental and social initiatives, however, the rate of migrants and refugees has grown significantly in recent years in the world, in this sense, the project provides an opportunity to disseminate information on the subject of migration, in order to broaden discussions on migration and refuge not only in extension, but also to extend this dialogue to teaching and research. We believe that extension activities provide a learning space that contributes significantly to both academics, teachers and especially the community served. In this way, the extension is seen as a privileged space for the formation of the human being, in the sense of preparing him for life in society, that is, not only preparing for an area of ​​activity, but to face new challenges and make it you a conscientious citizen. Keywords: Migration. University Extension. Citizenship.